1786 N.H. Laws 409-10, An Act for Forming and Regulating the Militia within this State, and for Repealing All the Laws Heretofore Made for that Purpose, § 7. - (:unkn) unknown (General Publisher, 1786)
[E]very non-commissioned officer and soldier, both in the alarm list and training band, shall be provided, and have constantly in readiness, a good musket, and a bayonet fitted thereto, with a good scabbard and belt, a worm, priming-wire and brush, a cartridge-box that will hold at least twenty-four rounds, six flints, and a pound of powder, forty leaden balls fitted to his gun, a knap sack, a blanket, and a canteen that will hold one quart.
--
Keywords: ARMED FORCES